Analisis Pengaruh CR, DER dan NPM Terhadap Pertumbuhan Laba Perusahaan (Studi Kasus pada Perusahaan Sektor Logistik dan Transportasi yang Terdaftar di BEI Periode 2019-2022) - Arif Rahman; Fajri Ariandi; Roynaldi Arista; Dani Chandra Utama; Warsono (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2025)
Every company certainly wants optimal profits in its business. This makes the company strive to carry out good management to achieve this goal. By doing this good management, the company can generate profit growth that always increases in each period. One way that can be done to predict the growth of a company's profit is by analyzing financial ratios. This study aims to analyze the partial and simultaneous effects of the current ratio, debt to equity ratio and net profit margin on profit growth in logistics and transportation sector companies listed on the Indonesia Stock Exchange for the 2019-2022 period. The data collection methods in this study are observation, literature study and documentation study with management or quantitative analysis methods, namely data analysis methods using descriptive statistical analysis, classical assumption tests from selected models, namely normality tests, heteroscedacity tests, multicollinearity tests, autocorrelation tests, and multiple linear regression analysis, determination coefficient tests and partial hypothesis tests (t-test) and simultaneous (t-test) assisted by the SPSS version 25 program. The data used is secondary data obtained from the Indonesia Stock Exchange website. Partially, the results in this study show that the current ratio variable does not have a significant effect on profit growth, the variable debt to equity ratio ratio has no significant effect on profit growth and the net profit margin variable has a significant effect on profit growth. Simultaneously, the variables current ratio, debt to equity ratio and net profit margin together affect profit growth. equity ratio and net profit margin together affect profit growth.